The influence of vermicomposting on photosynthetic activity and productivity of maize (Zea mays L.) crop under semi-arid climate. - Muhammad Younas; Huasong Zou; Tasmia Laraib; Waseem Abbas; Muhammad Waqar Akhtar; Muhammad Naveed Aslam; Luqman Amrao; Shoukat Hayat; Tariq Abdul Hamid; Akhtar Hameed; Ghalib Ayaz Kachelo; Mona M Elseehy; et al. (PLoS ONE, 2021)
Food production and waste recycling are the two major issues faced globally with rapidly increasing population. Recycling organic wastes to crop amendments could be a possible solution to these issues. Earthworms transfer organic waste to compost, which is used to grow crops and increase crop productivity. This study assessed the impact of vermicompost produced from the residues of six desert plant species, i.e., (Ziziphus mauritiana, Aerva javanica, Calligonum comosum, Sacchrum benghalens, Calligonum polygonoides and Prosopis cineraria) combined with farmyard manure (5 t ha-1) on growth, yield and photosynthetic activity of maize crop. Earthworm species Eisenia fetida (Savigny, 1826) was used to prepare vermicomposting of all tested plant species. The desert species were collected from natural habitats, chopped, dried, mixed with FYM and then earthworms were released to prepare the vermicompost. The earthworms were excluded twenty days after release and resultant was considered as compost and used in the experiment. Results revealed that application of P. cineraria vermicompost resulted in the highest plant height (75.33 cm), stem diameter (22.66 mm), cob length (17.66 cm), number of grains/cob (374.67), 1000-grain weight (260.41 g) and grains yield (3.20 t/ha). Application of P. cineraria vermicompost resulted in the highest uptake of macronutrients, i.e., N (91.01%), P (22.07%), K (80.41%), micronutrients, i.e., Fe (19.07 ppm), Zn (40.05 ppm), and phenolic contents (150). Application of P. cineraria vermicompost also resulted in the highest quantum photosynthetic yield (0.42 mole C/mole of photon), chlorophyll florescence (355.18 moles of photon m-2s-1) and electron transport rate (310.18 micro mole m-2s-1). It is concluded that vermicomposting has the potential to improve growth and yield of maize crop. Particularly, application of vermicompost obtained from P. cineraria can be used to improve the growth and yield of maize crop. Nonetheless, field trials are necessary for a wide scale recommendation.